Zimbabwean hospitality students’ experiences of sexual harassment in the hotel industry - Mkono, Muchazondida (Elsevier, 2021)
This study investigates the experiences of Zimbabwean hospitality management students in relation to sexual harassment. The students were asked to draw their responses from their industrial attachment year which is part of their four-year degree program. Guided interviews were conducted with 77 final year hospitality management students who had undertaken their industrial attachment in the hotel industry. Findings reveal that sexual harassment is not uncommon in Zimbabwean hotel workplaces. Coworkers, managers and customers were identified as perpetrators. The lack of sexual harassment training in the Zimbabwean hospitality, as well as the non-response of managers to some sexual harassment cases are possible indicators of the inadequacy, or complete lack of sexual harassment policies in Zimbabwe's hotel industry. The researcher suggests that human resource managers in the hotels should formulate, in consultation with Zimbabwean law and labour relations experts, sound sexual harassment policies. Continuous educational training for all employees and managers is also necessary to encourage more employees to report cases and to deter offenders.